Home-based record (HBR) ownership and use of HBR recording fields in selected Kenyan communities: Results from the Kenya Missed Opportunities for Vaccination Assessment - Brown, David W. (PLoS One, 2018)
BACKGROUND: Home-based records (HBRs), which take many forms, serve as an important tool for frontline health workers by providing a standardized patient history vital to making informed decisions about the need for immunization services. There are increasing concerns around HBRs with recording areas that are functionally irrelevant because records are incomplete or not up-to-date. The aim of this report was to describe HBR ownership and report on the utilization of selected recording areas in HBRs across selected study communities in Kenya. METHODS: The Kenya Missed Opportunities for Vaccination Assessment utilized a mixed-methods approach that included exit interviews, using a standardized questionnaire, among a convenience sample of caregivers of children aged <24 months attending a health facility during November 2016 as well as interviews of health staff and facility administrators. In addition to the exit interview data, we analysed data obtained from a review of available HBRs from the children. RESULTS: A total of 677 children were identified with a valid date of birth and who were aged <24 months. A HBR was in hand and reviewed for three-quarters of the children. Nearly one-third (n = 41) of those without a HBR in hand at the visit noted that they did not know the importance of bringing the document with them. Roughly two-thirds (n = 443) of caregivers noted they were asked by clinic staff to see the HBR during the clinic visit. Across the 516 reviewed HBRs, recording areas were most commonly identified for the child’s demographic information (80% of HBRs) and vaccination history (82%) with information marked in >90% of records. Recording areas were less frequently available for child early eye / vision problems (61%), growth monitoring (74%) and vitamin A (76%); with information marked in 33%, 88% and 60% of records, respectively. CONCLUSIONS: Critical to the reduction of missed opportunities for vaccination, the HBR’s importance must be emphasized and the document must be requested by health workers at every health encounter. Health workers must not only ensure that all children receive a HBR and counsel caregivers of its importance, but they must also ensure that all sections of the record are legibly completed to ensure continuity of care. Programmes are encouraged to periodically review and critically assess the HBR to determine whether the document’s design and content areas are optimal to end user needs.